Grounding and improving assessment in higher education: a way of promoting quality education - Isabel Fialho; Marília Cid; Marcelo Coppi (Frontiers in Education)
Assessment continues to be one of the topics that most concern teachers and most dissatisfies students. In this paper we describe and evaluate the impact of the training course “Grounding and Improving Pedagogical Assessment in Higher Education,” based on a descriptive survey questionnaire, applied in a convenience-selected sample of 31 teachers from a public university in Portugal, who participated in the pedagogical training course. The questionnaire was applied before the beginning of the course (pre-test) and after its completion (post-test). Data were analyzed using statistical procedures that consisted of frequency analysis and non-parametric analysis, using the Mann–Whitney and Wilcoxon tests. The results revealed several changes in teachers’ conceptions of assessment and demonstrated the positive impact of the course, since the comparison of the pre and post-test results showed that relevant changes occurred towards the most current theories of pedagogical assessment, being more significant in the group of teachers without pedagogical training.